The psychological advantage of unfalsifiability the appeal of untestable religious and political ideologies. [article]. - Friesen, Justin P.; Campbell, Troy H.; Kay, Aaron C.
We proposed that people may gain certain ?offensive? and ?defensive? advantages for their cherished belief systems (e.g., religious and political views) by including aspects of unfalsifiability in those belief systems, such tah some aspects of the beliefs cannot be tested empirically and conclusively refuted. This may seem peculiar, irrational, or at least undesirable to many people because it is amused that the primary purpose of a belief is to know objective truth. However, past research suggests that accuracy is only one psychological motivation among many, and falsifiability or testability may be less important when the purpose of a belief serves other psychological motives (e.g., to maintain one?s worldviews, serve an identity). In Experiments 1 and 2 we demonstrate the ?offensive? function of unfalsifiability: that it allows religious adherents to hold their beliefs with more conviction and political partisans to polarize and criticize their opponents more extremely. Next we demonstrate unfalsifiability?s ?defensive? function: when facts threaten their worldviews, religious participants frame specific reasons for their beliefs in more unfalsifiable terms (Experiment 3) and political partisans construe political issues as more unfalsifiable (?moral opinion?) instead of falsifiable (?a matter of facts?; Experiment 4). We conclude by discussing how in a world where beliefs and ideas are becoming more easily testable by data, unfalsifiability might be an attractive aspect to include in one?s belief systems, and how unfalsifiability may contribute to polarization, intractability, and marginalization of science in public discourse. - - (from the authors)